Private Yokoi's War and Life on Guam, 1944-1972 The Story of the Japanese Imperial Army's Longest WWII Survivor in the Field and Later Life - Hatashin, Omi (Brill, 2009)
When discovered by local hunters on Guam, Yokoi was widely reported as a 'no surrender man' who survived, living up to the old Japanese military code of honour. This book sheds light on the reality of the war in the Pacific while addressing some key issues concerning the nature of Japanese culture in modern times.; Readership: General/trade